2005
DOI: 10.1586/17434440.2.4.445
|View full text |Cite
|
Sign up to set email alerts
|

Alternative bearing surfaces in total hip arthroplasty

Abstract: Total hip arthroplasty continues to be one of the most effective surgical procedures currently available. The longevity of this otherwise very successful procedure is compromised by the wear of the bearing surface. In recent years, great advances have been made in the design of bearing surfaces that poise to offer extended performance to these artificial joints. The purpose of this review is to discuss the recent technologic advances in bearing surfaces and offer an insight to the potential benefits and concer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 93 publications
0
6
0
Order By: Relevance
“…Recessing the bearing reduces ROM and causes metal-on-metal impingement and wear, 13 whereas as metal-on-ceramic impingement may be better tolerated. 39 We found alumina ceramic-on-ceramic bearings reliable and safe in a diverse patient population, with an average patient age younger than 50 years and with more than 75% of the patients aged 60 years or younger at the time of surgery. The absence of osteolysis was very promising, and implant-related problems were infrequent.…”
Section: Figmentioning
confidence: 82%
See 1 more Smart Citation
“…Recessing the bearing reduces ROM and causes metal-on-metal impingement and wear, 13 whereas as metal-on-ceramic impingement may be better tolerated. 39 We found alumina ceramic-on-ceramic bearings reliable and safe in a diverse patient population, with an average patient age younger than 50 years and with more than 75% of the patients aged 60 years or younger at the time of surgery. The absence of osteolysis was very promising, and implant-related problems were infrequent.…”
Section: Figmentioning
confidence: 82%
“…Several alternative bearings have been used clinically to reduce wear and osteolysis. 39 The alternatives include cross-linked polyethylene acetabular liners, metal-on-metal bearings, and alumina ceramic-onceramic bearings. Although metal-on-cross-linked polyethylene is most commonly used, these bearings have the shortest clinical experience of the available alternative bearings.…”
mentioning
confidence: 99%
“…In recent years, an increasing number of alternative bearing surfaces have been used in THA [21,22]. These surfaces include ceramic on highly crosslinked polyethylene, metal on metal (MOM), and ceramic on ceramic (COC).…”
Section: Introductionmentioning
confidence: 99%
“…Some authors have suggested that limitations in manufacturing technology may have resulted in inconsistent and suboptimal dimensions of these early-generation metal-on-metal prostheses [23][24][25], leading to excessive friction, seizing and implant loosening. While the importance of consistent component sphericity and avoidance of equatorial articulation (a condition where the acetabular inner diameter is smaller than the outer diameter of the femoral head, leading to loading of the rim-head interface, see Figure 1) have been demonstrated in in vitro studies, neither of these phenomena have been consistently demonstrated in an ana lysis of explanted failed implants [26].…”
Section: Origins Development and Resultsmentioning
confidence: 99%
“…The importance of consistent and accurate head-cup clearance has been recognized as an important contributor to wear in large-diameter metal-on-metal bearings. While low bearing clearance is beneficial in terms of reducing wear rates, and increasing clearance from 100 µm by as little [15] Second-generation stemmed total hip arthroplasty Berton et al (2010) 100 (92) High-tolerance CoCrMo 43 Uncemented Uncemented 92 [34] Long et al (2010) 207 (181) High-tolerance CoCrMo 19 (12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24) Uncemented Uncemented 85 [35] Neumann et al…”
Section: Search Strategymentioning
confidence: 99%